STUDI PERBANDINGAN ANALISIS SCWB PADA SRPMK MENGGUNAKAN KONSEP BALOK PERSEGI DAN BALOK T - Salsabila Miyazumi Amri; Suranta Sembiring; Riesang Wirawan Probogumilang (Racic : Rab Construction Research, 2024)
Indonesia is one of the countries with the greatest risk of earthquakes in the world. Earthquakes that can damage or even collapse buildings make building design have to be earthquake resistant. Therefore, buildings must be designed respect to SNI 1726:2019 and SNI 2847:2019 earthquake resistant building planning standards. This study will investigate the comparison of the SMF structural design with two types of modelling concepts, namely the rectangular/conventional beam concept and the T-beam concept in the form of a comparison of reinforcement requirements, SCWB ratio, and structure performance level. This study was conducted in a five-story office building located in the city of Bandung which stands on soft soil. From the results of the calculation analysis, it was found that the column and plate reinforcement requirements were the same for both types of modelling concepts. Beam reinforcement requirements with the concept of rectangular beam modelling is higher than the concept of T-beam modelling. The SCWB ratio with the rectangular beam modelling concept is smaller than the SCWB ratio with the T-beam modelling concept. The SCWB ratio obtained by re-analysis using T-beams in the rectangular beam modelling design will be significantly reduced (20-35%) and there is even a SCWB ratio that is not qualified because it is less than 1.2. By pushover analysis, the performance level is according to ATC-40 and FEMA-440, for structures with rectangular beam modelling concept classified to damage control and for structures with T beam modelling concept classified to immediate occupancy.